An Improved Correction Technique for the Prediction of the Dynamic Response of a Beam under a Moving Vehicle - Nguyen, Duy Hung; Diem, Nguyen Dang; Pham, Thi Kieu (Engineering, Technology & Applied Science Research, 2023)
This study presents a correction approach that can capture the discontinuities in the bending moment and shear force in the dynamic analysis of beam-like structures traveled by a moving vehicle. The proposed approach was based on the Dynamic Modal Acceleration Method (DyMAM) to correct the dynamic response of the supporting structure with a reduced number of vibration modes. The use of a two-axle vehicle model was adopted to consider the pitching effect in the presence of surface irregularity and damping. The interacting forces between the beam and vehicle were filtered to avoid undesirable high-frequency contributions. Subsequently, a new formulation for the entire vehicle-beam system was obtained. The corresponding equation was solved using the Newmark numerical scheme to obtain the system responses in each time step. A numerical example was illustrated, showing that the proposed method was in close agreement with previous correction solutions in the vehicle-beam interaction analysis.